2020
DOI: 10.1371/journal.pone.0238978
|View full text |Cite
|
Sign up to set email alerts
|

The role of gambling type on gambling motives, cognitive distortions, and gambling severity in gamblers recruited online

Abstract: The recent literature shows that the type of gambling practiced influences problem gambling. This study was aimed at investigating the factors associated with gambling type, including gambling severity, gambling motives, and cognitive distortions. A total of 291 regular male gamblers (229 skill gamblers and 62 mixed gamblers, i.e., those who play at least one game of chance and one skill game) were recruited online and assessed for gambling severity (South Oaks Gambling Screen), gambling motives (Gambling Moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…When it comes to cognitive distortions, they are continuously confirmed as significant predictors of problem gambling and as a fundamental part of problem gambling symptomatology [ 70 , 85 , 86 , 87 , 88 , 89 , 90 ]. Consequently, approaches that challenge cognitive distortions and provide educational corrections have shown success in the treatment of problem gambling [ 85 , 91 ].…”
Section: Discussion and Study Limitationsmentioning
confidence: 99%
“…When it comes to cognitive distortions, they are continuously confirmed as significant predictors of problem gambling and as a fundamental part of problem gambling symptomatology [ 70 , 85 , 86 , 87 , 88 , 89 , 90 ]. Consequently, approaches that challenge cognitive distortions and provide educational corrections have shown success in the treatment of problem gambling [ 85 , 91 ].…”
Section: Discussion and Study Limitationsmentioning
confidence: 99%
“…Several studies have reported high levels of anxiety and depression in GD ( 24 , 52 ). Depression severity has even been predicted by gamblers involved in multiple online activities ( 53 ). The results are in line with these findings with high scores on the STAI and BDI-II.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to give information on their demographics (age, gender) and gambling behaviors including the game type which allowed a comparison between pure poker players and mixed gamblers. It was, for instance, reported that gamblers who play skills and luck games had higher gambling severity scores and higher coping motivation for gambling than skill gamblers [28]. They also completed assessments of possible gambling-related debts in the past 12 months (adapted from the South Oaks Gambling Screen [29]) as well as the following measures:…”
Section: Methodsmentioning
confidence: 99%